Chain growth mechanism on bimetallic surfaces for higher alcohol synthesis from syngas - Wang, Jingbo (2015)
Density function theory calculations are performed to investigate the chain growth mechanism on bimetallic surfaces during the syngas conversion. The weighted d-band center correlates well with the adsorption energy of two reactants on bimetallic surface. The boundary between Cu and Co domains facilitates the association reaction of chain growth. Particularly, the reduction of barrier for CO insertion step accelerates the formation of acyl intermediate and thus provides paths to higher alcohol synthesis. The present work demonstrates the synergistic effect in the bimetallic surface from the microscopic view.